2020
DOI: 10.3390/agronomy11010039
|View full text |Cite
|
Sign up to set email alerts
|

Italian Ryegrass (Lolium multiflorum Lam.) Fiber Fraction Content and Dry Matter Digestibility Following Biostimulant Application against the Background of Varied Nitrogen Regime

Abstract: An experiment was conducted to determine the effect of an application of biostimulants, against the background of varied nitrogen regime, on the share of neutral detergent fraction (NDF), acid detergent fraction (ADF), and acid detergent lignin (ADL) in the crude fiber fraction of Italian ryegrass as well as its digestibility. A field experiment was arranged as a randomized subblock design (split-plot) with three replicates at the Siedlce Experimental Unit of the University of Natural Sciences and Humanities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…In addition, their increased levels as an effect of exogenous application in plants indicate improved functioning of the defense system against biotic and abiotic stresses [87]. This is in agreement with the results reported by Godlewska et al [77,88], who noted that the application of plant extracts induced a change in the fatty acid profile in cabbage and celery root crops [79]. A study on the application of garlic extracts in pepper cultivation conducted by Hayat et al [28] demonstrated that the extracts mitigated lipid peroxidation and thus prevented the formation of oxidation products inhibiting the activity of membrane enzymes and transport proteins.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, their increased levels as an effect of exogenous application in plants indicate improved functioning of the defense system against biotic and abiotic stresses [87]. This is in agreement with the results reported by Godlewska et al [77,88], who noted that the application of plant extracts induced a change in the fatty acid profile in cabbage and celery root crops [79]. A study on the application of garlic extracts in pepper cultivation conducted by Hayat et al [28] demonstrated that the extracts mitigated lipid peroxidation and thus prevented the formation of oxidation products inhibiting the activity of membrane enzymes and transport proteins.…”
Section: Discussionsupporting
confidence: 89%
“…Algex biostimulant to Italian ryegrass produced the most beneficial response in terms of the share of NDF, ADF, and ADL fractions in the plant dry matter. Increasing nitrogen rates significantly reduced the quantity of analyzed fiber fractions, and increased grass digestibility [11].…”
Section: Introductionmentioning
confidence: 95%
“…Effective strategies are needed to prevent excess accumulation of mineral nitrogen (N) in soil [5]. There are reports suggesting that it is possible to replace, at least in part, the application of nitrogen fertilisation with the application of biostimulants to forage grasses [6]. The use of N fertilisers should also be reduced to cut nitrogen oxide emissions [7].…”
Section: Introductionmentioning
confidence: 99%